Seize the advantages of cardiac rehabilitation - Yahui Zhang; Shangwei Huang; Bin Liu; Ying Li (Annals of Medicine)
Background Cardiac rehabilitation (CR) is a multidisciplinary intervention encompassing medical therapy, exercise training, nutritional guidance, psychological support, and smoking cessation. While CR demonstrates proven efficacy in controlling cardiovascular risk factors, improving myocardial ischemia, and reducing mortality in cardiovascular disease (CVD) patients, its global adoption rate remains critically low despite these established benefits.Core Components As the cornerstone of CR, sports training programs not only enhance muscular strength, systemic endurance, and cardiopulmonary fitness but also yield significant secondary benefits, such as ameliorating cognitive impairment and depressive symptoms, improving balance and coordination, and facilitating behavioral modification for sustainable lifestyle changes. These synergistic effects collectively optimize patients’ physiological, psychological, and social functioning.Clinical Significance For CVD patients, CR serves as a vital transitional phase, accelerating functional recovery, improving quality of life, and promoting successful societal reintegration.